2011
DOI: 10.3327/jnst.48.384
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Measured Isotopic Compositions of High-Burnup BWR MOX Fuel

Abstract: Analysis of measured isotopic compositions of four high-burnup BWR MOX fuel samples was performed by using a general-purpose neutronic calculation code SRAC and a continuous-energy Monte Carlo burnup code MVP-BURN. The initial Pu fissile content of the samples was 5.52 wt%, and the burnups ranged from 50 to 80 GWd/t. It is confirmed that a geometrical model including the effect of UO 2 assemblies adjacent to the MOX assembly is necessary in the burnup calculations to obtain accurate calculated isotopic composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 11 publications
(7 reference statements)
2
8
0
Order By: Relevance
“…The measured inventories provided the burnup of the measured fuel sample by applying Neodymium-148 Method [12]. Ando et al reported the burnup value of the sample as 69.90 GWd/t [13]. They used the measured isotopic inventories of actinide nuclides and 148 Nd, and the effective values of MeV/fission and fission yield of 148 Nd which were calculated by a continuous energy Monte Carlo burnup calculation code MVP-BURN [14,15].…”
Section: Comparison Between Calculated and Measured Inventoriesmentioning
confidence: 99%
See 3 more Smart Citations
“…The measured inventories provided the burnup of the measured fuel sample by applying Neodymium-148 Method [12]. Ando et al reported the burnup value of the sample as 69.90 GWd/t [13]. They used the measured isotopic inventories of actinide nuclides and 148 Nd, and the effective values of MeV/fission and fission yield of 148 Nd which were calculated by a continuous energy Monte Carlo burnup calculation code MVP-BURN [14,15].…”
Section: Comparison Between Calculated and Measured Inventoriesmentioning
confidence: 99%
“…This value for 241 Am seems to be unreasonably high. In the MALIBU program, where two or three different organizations including SCK/ CEN participated in chemical assay of fuel samples, the other organization reported 10% and 17% larger measurement data of the total Am weight for the samples taken from the axially-adjacent parts in the fuel rod [13]. The other prominent C/Es are seen for some of the metallic FP nuclides, 99 Tc, 101 Ru, 108 Pd, and 109 Ag, which cause considerable contributions due to the C/Es of 1.267, 1.424, 1.300, and 1.260, respectively.…”
Section: Correction Of Isotopic Inventories In Irradiated Mox Bundlementioning
confidence: 99%
See 2 more Smart Citations
“…As part of the above-mentioned validation study (i), the Japan Nuclear Energy Safety Organization has been participating in the international program MALIBU [2] on the measurement of isotopic compositions in high-burnup spent fuels discharged from light water reactors and performing neutronic analyses of the measurement data [3].…”
Section: Introductionmentioning
confidence: 99%